Posouzení informačního systému firmy a návrh změn - Gajdoš, David (Vysoké učení technické v Brně. Fakulta podnikatelská, 2020)
Práce má za úkol analyzovat současný stav informačního systému firmy, odhalit jeho slabé stránky, poté prozkoumat teoretické možnosti a následně navrhnout vylepšení tohoto systému.

This dissertation is aimed to analyze current status of the company information system, to reveal it's weak points, then to explore theoretical possibilities of a solution and finally to design a new solution of information system.
Assessment of Information System for a Company and Proposal for Amendments
Keywords: informační systém; proces; management procesů; server; projekt implementace; information system; process; process management; server; implementation project